Patient-Reported Outcome Measures in Inpatient Spine Care: A Prospective Pilot Study on Feasibility and Process Integration - Anna Tiedt; Isabell Weber; Dina Wiersbicki; Christoph-Eckhard Heyde; Anna Völker (Zeitschrift für Orthopädie und Unfallchirurgie, 2026)
Abstract Patient-reported outcome measures (PROMs) are key instruments in value-based healthcare but are not yet routinely implemented in inpatient clinical practice. This prospective pilot study aimed to evaluate the organizational feasibility and integration of a digital PROM collection in a university spine center. In this prospective pilot study, consecutive patients scheduled for elective inpatient conservative or surgical spine treatment were included. PROMs were collected digitally via tablet at two time points: at admission (T1) and prior to discharge (T2). Both generic and disease-specific PROMs were used. Primary endpoints were participation rate, data completeness, and process-related barriers. In addition, usability of the software was assessed using the System Usability Scale (SUS). Of 225 screened patients, 144 (64%) were included. PROM collection at admission was complete (100%), whereas complete data at discharge (T2) were available for 62.5% of patients. The main reason for incomplete data was failure to administer the survey during the discharge process (n = 44). The majority of patients were digitally contactable and preferred email contact for potential follow-up assessments. Usability of the software was rated high (median SUS score 87.5). PROM trajectories showed overall clinically plausible changes. Digital PROM collection in routine inpatient care is feasible and can be successfully integrated into clinical workflows. However, the discharge process represents a critical point of data loss. Structured integration into routine processes, including defined responsibilities and workflow-based triggers, appears necessary to improve data completeness.